Public Sector Corporate Social Investments in Namibia: The Case of the Mobile Telecommunications Company - Ralph Marenga (Administrative Sciences)
A bias in research has seen studies focus mostly on corporate social investments (CSIs) in the private sector. The current study aims to provide an alternative perspective to the traditional association of CSIs with private sector organisations by including public sector entities such as public enterprises (PEs), using the case of the Mobile Telecommunications Company (MTC) in Namibia. A qualitative research method and a single case study research design focusing on MTC was used, and data were analysed through themes and deductive reasoning. The major findings of this study show that MTC is exemplary in practicing CSI in Namibia’s public sector. MTC has various impactful socio-economic and environmental focus areas of CSI, which contribute to the development agenda of the Namibian government. The issue of CSI in the public sector is intriguing and could be usefully explored in further research, particularly from a developing country perspective. It is now possible to conclude that PEs can also be dominant players in the CSI sphere, particularly from a public sector perspective. The findings in this study make important contributions to the literature by providing a public sector institutional perspective of CSI that is different from the traditional view that mostly associates CSIs with the private sector.